The girl I was : a novel [large type] - Rose, Jeneva (Thorndike Press large print top shelf., 2025)
"When Alexis Spencer loses her job and her relationship on the same day, she finds a bottle of vodka from her college days and goes on a bender, blacking out in the process. Only this time, she doesn't wake up at home, or in the right city. In fact, she isn't even in the right year. Alexis is back in her college town in the year 2002. She heads to her dorm--and comes face-to-face with her eighteen-year-old unruly self, who goes by Lexi. They might be the same person, but they couldn't be more different from one another. Now Alexis and Lexi must come to terms with the fact that alone, they will never make things right, but together, they could change their life for the better"--